Characterisation of oxidative injury to an intestinal cell line (HT-29) by hydrogen peroxide. Issue 11 (November 1994) - Watson, A J; Askew, J N; Sandle, G I
Abstract : Reactive oxygen metabolites have been implicated in causing epithelial cell injury in colonic inflammation. A model of oxidant injury in intestinal epithelial cells has been developed in which HT-29-18-C1 cells are injured with graded concentrations of hydrogen peroxide and characterised by the MTT test. The MTT test was validated as a cytotoxicity assay and has a similar sensitivity to hydrogen peroxide induced injury as the assay of intracellular adenosine triphosphate. Exposure to a range of hydrogen peroxide concentrations (0.05-20 mM) for varying duration (5-120 min) showed that injury was dependent on time and concentration. The median lethal dose (LD50) for one hour exposure to hydrogen peroxide was approximately 0.1 mM. Injury from hydrogen peroxide was only partially reversible as determined by the MTT test and assay of cellular proliferation by crystal violet staining. There was an exponential loss of hydrogen peroxide when incubated with HT-29-18-C1 cells (t1/2 35 min). Experiments with 0.5 mg/ml aminotriazole and 0.5-2 mM buthionine sulphoximine suggested hydrogen peroxide breakdown was predominantly caused by catalase rather than glutathione peroxidase. Injury resulting from 1 mM hydrogen peroxide could be reduced by either coincubation of cells with 1, 10-phenanthroline, an Fe2+ chelator, or preincubation with deferoxamine, and Fe3+ chelator, suggesting the participation of Fe2+ and Fe3+ in hydrogen peroxide induced injury. In conclusion, hydrogen peroxide induces injury in HT-29-18-C1 cells both directly and by generation of the hydroxyl radical.